Goals (th)at work: Goals, monetary incentives, and workers' performance - Sebastian J. Goerg; Sebastian Kube (Max Planck Institute for Research on Collective Goods, 2012)
In a randomized field experiment, we investigate the connection between work goals, monetary incentives, and work performance. Employees are observed in a natural work environment where they have to do a simple, but effort-intense task. Output is perfectly observable and workers are paid for performance. While a regular piece-rate contract serves as a benchmark, in some treatments workers are paid a bonus conditional on reaching a pre-specified goal. We observe that the use of personal work goals leads to a significant output increase. The positive effect of goals not only prevails if they are self-chosen by the workers, but also if goals are set exogenously by the principal - although in the latter case, the exact size of the goal plays a crucial role. Strikingly, the positive effect of self-chosen goals persists even if the goal is not backed up by monetary incentives. We propose a novel incentive contract where - through the choice of a personal work goal - workers themselves determine the risk and the size of their bonus payment at the same time.
Keywords: A12; C93; D01; D03; D24; J24; J33; M52; 330; Goal setting; monetary incentives; bonus payments; pay-for-performance contracts; workplace behavior; field experiment; Leistungsentgelt; Akkordlohn; Betriebswirtschaftliches Ziel; Arbeitsleistung; Feldforschung; Deutschland